Innovative pit design and sludge dewatering for rural areas. Issue 4 (December 2016) - Hamawand, Ihsan; Lewis, Larry
Abstract: This article addresses an innovative pit design and sludge dewatering in rural areas in developing countries. The innovative pit design which also function as sludge dewatering system is low cost, easy to implement and highly efficient. The system uses a mobile metal cage lined with a filter bag to collect the sludge. Based on this design, emptying the pit and transporting the dewater sludge is far much cheaper and easier than current practice (using vacuum trucks). The dewatering technique uses time instead of pressure to dewater the sludge. The results showed that a pit with 4 m 3 capacity can save the owner the cost of emptying the pit and 83% the cost of transporting the sludge via current method. It also saves the water treatment plant around 50 cost of dewatering the sludge from a single pit using dewatering machines.